Bayesian and Dominant-Strategy Implementation in the Independent Private-Values Model - Manelli, Alejandro M.; Vincent, Daniel R. (Econometrica, 2010)
We prove—in the standard independent private-values model—that the outcome, in terms of interim expected probabilities of trade and interim expected transfers, of any Bayesian mechanism can also be obtained with a dominant-strategy mechanism.